2022
DOI: 10.1111/imb.12758
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐3017b contributes to metamorphosis by targeting sarco/endoplasmic reticulum Ca2+ATPase in Tribolium castaneum

Abstract: In recent years, increasing numbers of microRNAs (miRNAs) have been reported to regulate insect metamorphosis. One thousand, one hundred fifty‐four miRNAs have been previously identified from Tribolium castaneum by high‐throughput sequencing; however, little is known about which miRNAs can participate in metamorphosis, leaving the role of miRNAs in regulating the underlying mechanism elusive. Here, we report the participation of miR‐3017b in the metamorphosis of T. castaneum. Temporal profiles revealed that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, inhibiting miR‐34 resulted in the up‐regulation of the main 20E signaling pathway genes, such as E75 , USP , EcR , Br‐C , and FTZ 25 . Overexpression of miR‐3017b or knockdown of SERCA altered the expression levels of 20E signaling genes such as ECR , USP , HR3 , and Br‐C 29 . These results suggest that 20E controlling the expression of miRNAs might play an important role in promoting the precision of the gene regulation network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inhibiting miR‐34 resulted in the up‐regulation of the main 20E signaling pathway genes, such as E75 , USP , EcR , Br‐C , and FTZ 25 . Overexpression of miR‐3017b or knockdown of SERCA altered the expression levels of 20E signaling genes such as ECR , USP , HR3 , and Br‐C 29 . These results suggest that 20E controlling the expression of miRNAs might play an important role in promoting the precision of the gene regulation network.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐276a‐3p was up‐regulated during the larval–pupal transition and its overexpression reduced developmental growth 27,28 . In T. castaneum , miR‐3017b and its target gene SERCA mediated the metamorphosis by regulating the 20E signaling pathway 29 . In Spodoptera exigua , miR‐4924 regulated larval development and molting 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The GO enrichment analysis showed that these DEmiRNAs mainly participate in the cytoplasm (32), plasma membrane (20), signal transduction (15), and sequence-specific DNA binding transcription factor activity (14) ( Figure 7 B). In the cluster, miR-9a targeting senseless ensures the precise specification of sensory organ precursors in Drosophila [ 55 ], and it also target the Drosophila transcriptional regulator LIM-only to prevent apoptosis during wing development [ 56 ]; miR-8 null flies are smaller in size and defective in insulin signaling in fat body [ 57 ], gain and loss of miR-8 provoked developmental defects reminiscent of impaired Notch signaling [ 58 ], and it also acts as a negative regulator of Wnt signaling to affect eye and wing development in D. melanogaster [ 59 ]; miR-252 has vital roles in growth, development and cell cycle of insect [ 9 , 60 , 61 ]; miR-3017 contributes to larval to pupal to adult metamorphosis by targeting sarco/endoplasmic reticulum Ca 2+ ATPase in T. castaneum [ 62 ]. Mutation of the Drosophila miR-6 cluster, which contains three miR-6 genes, showed a modest reduction in viability to adulthood [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In locusts, agomir-276 and antagomir-276 injection resulted in the advance and the delay of the hatching time, respectively (He et al, 2016). In Tribolium castaneum, overexpression of miR-3017b caused arrest of metamorphosis (Tang et al, 2022). In Drosophila melanogaster, overexpressing miR-315 caused pupation defects and reduced hatching rates (Yuan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Tribolium castaneum , overexpression of miR‐3017b caused arrest of metamorphosis (Tang et al. , 2022). In Drosophila melanogaster , overexpressing miR‐315 caused pupation defects and reduced hatching rates (Yuan et al.…”
Section: Introductionmentioning
confidence: 99%